HUBUNGAN PERAN KELUARGA DENGAN TINGKAT KECEMASAN ANAK USIA SEKOLAH YANG MENGALAMI HOSPITALISASI DIRUANG RAWAT INAP ANAK RUMAH SAKIT TINGKAT III DR.REKSODIWIRYO PADANG - Rika Syafitri (Ensiklopedia of Journal, 2021)
Based on the coud from Hospital Dr.Reksodiwiryo Padang number of children who are sick in the year 2017 as much 338 children. The results of the researchers initial survey through interviews, children in hospital many are not accompanied by family consequently the child feels anxiety show by crying and anxious children also because of hospital action like taking not to want to be acted and the hospital environment, especially the treatment room that causes anxiety. The purpose of this research is to know Relationship Family Role With Anciety Level School Age Children That Experience Hospitalization At Child Inpatient Room At Hospital Dr.Reksodiwiryo Padang 2018. This type of research is the research design with analytic deskriftif Cross Sectional Study. This research was in At Child Inpatient Room At Hospital Dr.Reksodiwiryo Padang 2018. Research and data collection is carried out from March 2018 through the month of August 2018, with the number of total 160 and samples of the 30 respondents, sampling techniques using accidental sampling. The data obtained were analyzed in univariate frequency distributions with and bivariat with statistical test Chi Square. The research univariat results obtained by family role not good (56,7%) with anciety level (43,3%). Results of bivariate research based on statistical test obtained that there is a meaningful relationship family role with anciety level pvalue=0,000. Recommended to the hospital so that employess in the hospital, especially the children room pay more attention to children in the room and provide nursing care to reduce anxiety. For parents can pay more attention to children when children experience treatment in the hospital so that more comfort will be created by the child and the level of anxiety experienced by the child can be slightly controlled.